Analysis of Deformation Characteristics of Dikes on Deep Soft Soil Foundations - WU Juan; ZHANG Ming; LI Yansong; HOU Weijian (Renmin Zhujiang)
The deformation of dikes directly affects the safety of dikes,especially for dikes on deep soft soil foundations,whose deformation is often large,and thus it is often used as the main evaluation index of dike safety.By the reconstruction project of a dike on soft soil foundations,the finite element numerical analysis model for the typical section of the dike is built,and the deformation of the dike during the completion period and under the characteristic water levels is calculated,with emphasis on analyzing the influence of the water level changes and pressure platform on the deformation characteristics of the dike.The results indicate that the dike settlement is severe,and the severe settlement area is mainly concentrated near the center of the surface layer of the dike foundation,and the soft foundation has a significant impact on the dike settlement.The horizontal deformation is relatively small,mainly concentrated in soft foundations,and the horizontal deformation of the dike body is slight.The pressure platform on the waterside slope and the water level changes near a river have a great influence on the horizontal deformation of the dike.On the whole,the dike design scheme is reasonable,and it is suggested to reserve a sufficient settlement amount at the top of the dike.